2019
DOI: 10.1021/acs.jctc.9b00693
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Second- and Third-Order Many-Body Green’s Function Methods with Frequency-Dependent, Nondiagonal Self-Energy

Abstract: We fully develop the Monte Carlo many-body Green’s function (MC-GF) method with the following enhancements: (1) The truncation order of the perturbation expansion of the Dyson self-energy is raised from the second order (MC-GF2) to the third order (MC-GF3) with the aid of a computerized procedure to enumerate and transform all 84 third-order Goldstone diagrams into Monte Carlo integrable expressions and then into central processing unit (CPU)/graphical processing unit (GPU)-parallel computer codes. (2) An effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This provision not only compresses the cost of propagating electron pairs (walkers) but also dramatically reduces the variance, as proven below. On the other hand, the distributions (weight functions) for the imaginary-time coordinates for dimer AB, monomer A, and monomer B are kept unchanged because they depend on the highest-occupied and lowest-unoccupied molecular orbital energies, 43 which differ from one subsystem to another. In the direct-sampling algorithm, 37 random imaginary times are generated directly from the distribution using a random number seed, p τ [n] .…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This provision not only compresses the cost of propagating electron pairs (walkers) but also dramatically reduces the variance, as proven below. On the other hand, the distributions (weight functions) for the imaginary-time coordinates for dimer AB, monomer A, and monomer B are kept unchanged because they depend on the highest-occupied and lowest-unoccupied molecular orbital energies, 43 which differ from one subsystem to another. In the direct-sampling algorithm, 37 random imaginary times are generated directly from the distribution using a random number seed, p τ [n] .…”
Section: ■ Methodsmentioning
confidence: 99%
“…All good practices of the state-of-the-art MC-MP2­(-F12) implementation were adopted in the supermolecular and concurrent MC-MP2­(-F12) methods for noncovalent interaction energies, including the redundant-walker, control-variate, and direct-sampling algorithms, as well as the stochastic imaginary-time integration . The reader is referred to these articles for the algorithm details.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DMQMC joins a growing set of methods including other quantum Monte Carlo methods, [6][7][8][9][10][11] many body theories [12][13][14] and others in attempting to solve the finite temperature problem that has attracted recent attention amongst quantum chemists. [15][16][17][18][19] Many of these methods, like DMQMC, continue to undergo development. [20][21][22][23][24][25][26][27][28] Widespread adoption of all methods in the FCIQMC family, including DMQMC, is hindered, in part, due to the sign problem.…”
Section: Introductionmentioning
confidence: 99%
“…This study along with the one reported in Ref. 59 have been conducted to lay a firm mathematical foundation of perturbation theories, 87,88 which continue to be a workhorse for efficient, converging ab initio electronic structure calculations [89][90][91][92][93][94][95][96][97][98][99][100][101] for large complex molecules and solids.…”
Section: Discussionmentioning
confidence: 99%